Genetic Stability and Public Health Implications of Plasmid-Free Vibrio cholerae: Stabilitas Genetik dan Implikasi Kesehatan Masyarakat dari Vibrio cholerae Bebas Plasmid - Mushtaq Talib Al-Safi (Academia Open, 2024)
Background: Cholera, caused by Vibrio cholerae, is a significant global health concern, particularly in regions with poor sanitation. Specific Background: This study focuses on V. cholerae strains isolated from cholera patients in Al-Nasiriyah city, Iraq, where limited genetic studies have been conducted. Knowledge Gap: Despite extensive research on V. cholerae, little is known about the genetic makeup of strains from Al-Nasiriyah city and their plasmid content, which traditionally correlates with antibiotic resistance and virulence. Aims: This research aimed to characterize the genetic and antibiotic resistance traits of V. cholerae strains from cholera patients in Al-Nasiriyah city and to determine the presence of plasmids using advanced molecular techniques. Results: Contrary to expectations, our study identified V. cholerae strains devoid of plasmids and exhibiting a stable genetic profile across two chromosomes, with sizes ranging from 1 to 3 million base pairs. Novelty: Our findings challenge conventional wisdom by demonstrating the absence of plasmids in local V. cholerae strains and highlighting their unique genetic architecture. Implications: This study underscores the importance of genomic diversity studies in understanding V. cholerae epidemiology and guiding public health strategies. Future research should explore larger strain cohorts and conduct comparative genomic analyses to elucidate the broader implications of genetic variability on cholera outbreaks and treatment strategies. Highlights: Genetic Stability: V. cholerae strains exhibit stable genetic profiles. Plasmid Absence: No plasmids found, challenging antibiotic resistance assumptions. Public Health Impact: Crucial for effective cholera management and prevention strategies. Keywords: Vibrio cholerae, genetic diversity, antibiotic resistance, plasmid absence, public health implications